P44. Motor unit loss in amyotrophic lateral sclerosis as detected by MSCAN occurs mainly in Phase I of the D50 disease progression model. Issue 8 (August 2018) - Hohmann, M.; Gaur, N.; Stubendorff, B.; Gunkel, A.; Rödiger, A.; Witte, O.W.; Grosskreutz, J.
Abstract : Background: MSCAN is a novel automated motor unit counting method based on threshold tracking. It assesses the excitability of individual motor units and was initially developed to address limitations with other estimation methods such as MUNE and MUNIX. The D50 progression model uses regularly collected ALSFRS-R scores to describe and to relate individual events within the ALS disease course and reduce noise associated with the ALSFRS-R and the conventional PR parameter. Objective: To quantify and longitudinally track motor unit loss in ALS patients relative to controls in a clinical setting in context of the D50 model. Methods: Threshold-tracking experienced staff performed measurements in 39 patients and 19 controls, in the ABP, ADM, and TA in the less affected side. Twenty and 12 patients made it to the first and second follow-ups, respectively. Measurements were correlated with a range of clinical parameters, including indices from the D50 model such as D50 (time taken for the individual's ALSFRS-R score to drop to 24) and rD50 (calculated value describing individual disease covered in relation to D50). Results: A strong correlation between CMAP amplitude and motor unit number was observed in all three muscles in all participants. ALS patients had significantly fewer motor units in the APB, ADM ( p < 0.001) and the TA ( p < 0.05); they also had a significantly lower CMAP in the APB and ADM. Both motor unit number and CMAP amplitude declined over time, albeit non-significantly. Motor unit numbers were significantly reduced in all three muscles in ALS patients in disease Phase 1 of the D50 model (APB & ADM p < 0.001, TA p < 0.01). Conclusions: MSCAN demonstrated a significant correlation between CMAP and motor unit numbers, and also revealed a longitudinal decline in both. MSCAN enabled distinction between ALS patients and healthy controls. Crucially, joint use with the D50 model revealed significant motor unit loss in Phase 1 i.e. early-stage disease, making MSCAN a potential diagnostic marker. Acknowledgment: This research is supported byBMBF (Bundesministerium für Bildung and Forschung) in the framework of the E-RARE programme (PYRAMID), JPND (OnWebDUALS) of the European Union, and theDt. Ges. für Muskelkranke (DGM).